Physiological potential of soybean seeds in west Bahia - Cavalcante, João Pedro Jacobsen (2022)
Given the importance of verifying the germination potential of the seeds, in order to subsidize the choice of the soybean cultivar to be installed in the field, the objective was to investigate the germination potential of the seeds 84185RSF IPRO (OH JURNA), SYN1687 IPRO , BRAMAX DOMÍNIO IPRO, NS 8400 IPRO and M 8349 IPRO, in field conditions in the West of Bahia. Soybean crop research together with the production of Barreiras-BA, a reference municipality of São Desidério in the Northeast region of Brazil. A randomized block design was used with five treatments (cultivars) and four blocks. Between the weight of a thousand seeds, the water content, the emergence (E), the emergence speed index (IVE) and the emergence speed (VE). The highest and lowest thousand seed weights were selected for seeds of cultivars 84185RSF IPRO and NS 8400 IPRO333, respectively. Soybean cultivars differ significantly in relation to emergence and emergence speed index. The seeds of the cultivar SYN 868 IPRO presented a lower physiological potential in relation to the seeds of the cultivars NS 8400 IPRO and M 8349 IPRO; what could happen to their establishment in the countryside, especially in unfavorable conditions.